Pregnancy-related reference intervals for serum thyrotropin based on real-life clinical data. (1st February 2021) - Canovi, Simone; Vezzani, Silvia; Polese, Alessandra; Frasoldati, Andrea; Schiatti, Clara; Preda, Cristina; Corradini Zini, Michele; Vitiello, Antonio; Foracchia, Marco; Comitini, Giuseppina; Aguzzoli, Lorenzo; Fasano, Tommaso; et al.
Abstract: Aim: During pregnancy, thyroid homeostasis is physiologically modified, leading to altered levels of thyrotropin (TSH): hence, the adoption of pregnancy-related, population- and method-specific reference ranges is recommended. This monocentric and retrospective study was conducted to establish local pregnancy-related reference intervals for serum TSH in singleton pregnant women using real-life clinical data. Methods: We included women who measured serum TSH during pregnancy at our Laboratory over six years, excluding pregnant women with current or past history of thyroid disease, pituitary or autoimmune diseases, use of medications known to influence thyroid function, multiple and/or pathological pregnancies, BMI >30 Kg/m 2 . Results: We retrieved a total of 3744 TSH results. Reference limits (90% confidence intervals) for TSH (in mIU/L) are: first trimester 0.09 (0.06–0.12) − 3.16 (3.05–3.29); second trimester 0.25 (0.11–0.30) − 3.55 (3.34–3.73); third trimester 0.42 (0.15–0.48) − 3.93 (3.80–4.08). Conclusion: In conclusion, real-life clinical data could be used to establish or verify local reference intervals for TSH in pregnant women: this may reduce the risk of misclassification of pregnant women undergoing thyroid function testing.